Advokasi dan Penyuluhan Bahaya Pelacuran Dini pada Remaja Wajo Baubau - Nurul Ahwat Rantekata; Hazmun Hazmun; Tamzir Tamzir; Haslizar Haslizar (Pusat Riset dan Inovasi Nasional, 2023)
This community service and research aims to increase public awareness of the importance of improving parenting patterns in families and provide an understanding of the health impacts of early prostitution behavior deviations. In addition, the community is also given legal education so that the community knows the consequences of early prostitution. This community service was carried out for two days, where the first day was a seminar and the second day met and greeted the community directly from house to house so that the community could consult directly for free. Students of the BPI STAI YPIQ Baubau study program also helped smooth the process of counseling activities by dividing tasks, some were in charge of the event section, consumption, and documentation so that the activities ran smoothly. The facts found in the field turned out that the community was still not aware of the dangers of early prostitution and their literacy was still very low, so the community service efforts that researchers and several stakeholders involved did greatly helped the community to be aware and careful with the environment and technological tools that could lead children into early prostitution deviations.